Impact of obstructive sleep apnea in transsphenoidal pituitary surgery: An analysis of inpatient data. (3rd July 2017) - Chung, Sei Y.; Sylvester, Michael J.; Patel, Varesh R.; Zaki, Michael; Baredes, Soly; Liu, James K.; Eloy, Jean Anderson
Abstract : Objectives/Hypothesis: Although previous studies have reported increased perioperative complications among obstructive sleep apnea (OSA) patients undergoing any surgery requiring general anesthesia, there is a paucity of literature addressing the impact of OSA on postoperative transsphenoidal surgery (TSS) complications. The aim of this study was to analyze postoperative outcomes in transsphenoidal pituitary surgery patients with OSA. Secondarily, we examined patient characteristics and comorbidities. Study Design: Retrospective analysis. Methods: The 2002 to 2013 National Inpatient Sample was queried for patients undergoing TSS for pituitary neoplasm. Patients with an additional diagnosis of OSA were identified, and compared to a non‐OSA cohort. Results: There were 17, 777 patients identified; 5.0% (N = 889) had an additional diagnosis of OSA. The OSA cohort had more comorbidities including diabetes mellitus, congestive heart failure, chronic pulmonary disease, coagulopathy, hypertension, hypothyroidism, liver disease, obesity, peripheral vascular disease, renal failure, acromegaly, and Cushing's syndrome. Postoperatively, OSA was independently associated with increased risks of tracheostomy ( P = .015) and hypoxemia ( P < .001), and decreased risk of cardiac complications ( P = .034). OSA patients did not have increased rates of cerebrospinal fluid rhinorrhea, diabetes insipidus, reintubation, aspiration pneumonia, infectious pneumonia, thromboembolic complications, or urinary/renal complications. In‐hospital mortality rates did not vary between the two cohorts. Conclusions: In patients who underwent transsphenoidal pituitary surgery, OSA was associated with higher rates of certain pulmonary and airway complications. OSA was not associated with increased non–pulmonary/airway complications or inpatient mortality, despite older average age and higher comorbidity rates. Level of Evidence: 2C. Laryngoscope, 128:1027–1032, 2018